2004
DOI: 10.1080/00365520310008818
|View full text |Cite
|
Sign up to set email alerts
|

Studies on tissue expression of HCV proteins (NS3 and C) in chronic hepatitis C using the ImmunoMax technique

Abstract: Anaemia associated with IBD can be successfully treated with intravenously administered iron sucrose, provided that bowel inflammation is treated adequately and enough iron is given. Treatment with iron sucrose is safe. Follow-up of haemoglobin and iron parameters to avoid further iron deficiency anaemia is recommended.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 4 publications
1
9
0
Order By: Relevance
“…The observed by us lack of correlation between HCV protein content on one hand and grading and staging of the process on the other reflects probably the very mild histological lesions in children. No such correlations have been noted also in adult patients with HCV infection, in whom inflammatory lesions and advancement of fibrosis were more pronounced than in children with hepatitis C (26, 32). Our studies have disclosed no correlation also between HCV protein content in situ and serum levels of HCV RNA, even if such a correlation has previously been shown by others for protein C (24).…”
Section: Discussionmentioning
confidence: 98%
“…The observed by us lack of correlation between HCV protein content on one hand and grading and staging of the process on the other reflects probably the very mild histological lesions in children. No such correlations have been noted also in adult patients with HCV infection, in whom inflammatory lesions and advancement of fibrosis were more pronounced than in children with hepatitis C (26, 32). Our studies have disclosed no correlation also between HCV protein content in situ and serum levels of HCV RNA, even if such a correlation has previously been shown by others for protein C (24).…”
Section: Discussionmentioning
confidence: 98%
“…Liao et al (2011) and Kasprzak et al (2004) reported that tissue expression of NS3 protein does not correlate with histological grade or stage of liver tissues or clinical features in patients with CHC. In our study, we did not find correlation between the number of cells expressing HCV NS3 protein and ALT, AST and METAVIR inflammatory grade and fibrosis stage.…”
Section: Discussionmentioning
confidence: 99%
“…It is thought that these subviral particles, which are produced at concentrations several logs above that of infectious virus particles, absorb neutralizing antibody and trigger immunological tolerance, both of which promote virus persistence in the blood. Moreover, in patients with CLD, there does not seem to be any correlation between intrahepatic HBsAg expression patterns and inflammatory infiltrates [16,17], nor have HBsAg specific T cell clones been isolated from such patients [18]. In addition, T cell sensitization to HBsAg in acute and chronic HBV infection is usually undetectable [19],…”
Section: Hepatitis B Surface Antigen (Hbsag)mentioning
confidence: 99%